2022
DOI: 10.1177/09544054221136528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanical and tribological properties of diamond-like carbon coatings doped with Europium and Gadolinium produced by HiPIMS

Abstract: Hydrogen-free diamond-like carbon (DLC) thin films can be employed for numerous applications, including engine components, once they exhibit good properties for that. They have been used as coatings due to their attractive properties, including high hardness, high wear resistance, and low CoF even under high load/pressure. One of the major limitations of hard hydrogen-free ta-C coatings applications is related to the low reactivity with oil additives used nowadays. The Ionic liquids (ILs) emerged as a novel cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…While most published studies focused on doping and/or alloying a-C coatings with metals or metalloids, doping a-C films with rare-earth elements and rare-earth oxides , has only recently been explored. As one example, Omiya et al, Sadeghi et al, and Shaikh et al evaluated the tribological properties of gadolinium (Gd)- and europium (Eu)-alloyed a-C films deposited by high power impulse magnetron sputtering (HiPIMS) in the presence of synthetic oil containing a class of promising additives for transmission fluids, namely phosphonium phosphate ionic liquids. , The results of tribological experiments and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) measurements indicated that only the introduction of Gd in the a-C matrix favors the formation of a transfer layer on the steel counterbody that enhances the generation and adhesion of a lubricious and antiwear boundary layer (i.e., tribofilm) from the lubricant additives .…”
Section: Introductionmentioning
confidence: 99%
“…While most published studies focused on doping and/or alloying a-C coatings with metals or metalloids, doping a-C films with rare-earth elements and rare-earth oxides , has only recently been explored. As one example, Omiya et al, Sadeghi et al, and Shaikh et al evaluated the tribological properties of gadolinium (Gd)- and europium (Eu)-alloyed a-C films deposited by high power impulse magnetron sputtering (HiPIMS) in the presence of synthetic oil containing a class of promising additives for transmission fluids, namely phosphonium phosphate ionic liquids. , The results of tribological experiments and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) measurements indicated that only the introduction of Gd in the a-C matrix favors the formation of a transfer layer on the steel counterbody that enhances the generation and adhesion of a lubricious and antiwear boundary layer (i.e., tribofilm) from the lubricant additives .…”
Section: Introductionmentioning
confidence: 99%
“…They include chemical substances that can adhere to and/or interact with solid surfaces to form protective, low-shear-strength reaction layers (referred to as "tribofilms"), which are intended to lower wear and friction [2]. Furthermore, diamond-like carbon (DLC) thin films have been shown to have high hardness and wear resistance and a low friction coefficient (CoF) [3,4], and to be biocompatible. DLC thin films, one of the most promising categories of surface engineering solutions, have been the subject of many investigations, specifically in the automotive industry.…”
Section: Introductionmentioning
confidence: 99%
“…The tribological behaviors of DLC films depend on external factors such as temperature, which results in various degrees of wear rates for the same film [5,6]. Several research projects have investigated the doping of DLC films with various metallic elements to further enhance their qualities and, primarily, to adjust some undesired traits, even beyond the good mechanical and tribological capabilities of currently available DLC coatings [4]. Usually, two categories of alloying materials are used to adjust the characteristics of DLC coatings: carbides (for instance, Ti, Cr, F, and W) and non-carbide formers (for example, Cu and Ag) [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations